THE USE AND ABUSE OF HIPPOCRATIC MEDICINE IN THE APOLOGY OF LUCIUS APULEIUS*. (20th July 2016) - Israelowich, Ido
Abstract : The Apology of Apuleius is a rare example of a complete forensic speech in Latin from the High Roman Empire. The prosecution on the charge of magia of a renowned rhetor in the court of a Roman proconsul, who might himself have been a distinguished Stoic philosopher, offers modern scholars a remarkable opportunity to observe an encounter between scholarship and legal practice. Apuleius arrived in the city of Oea en route to Alexandria as part of a life of learning and travel. While visiting Oea, Apuleius met his old schoolfriend Sicinius Pontianus, who encouraged him to wed his recently widowed mother Aemilia Pudentilla. The reason for this unusual request was Pontianus' wish that his mother would not marry someone unsuitable. Apuleius agreed and the marriage took place. However, it left Sicinius Aemilianus, a brother of Pudentilla's first husband, and Herennius Rufinus, Pontianus' father-in-law, aggrieved and they decided to pursue Apuleius through the courts. The Apology, which Apuleius later published as a record of his defence, has long attracted scholarly interest. Two commentaries have been published, the literary aspects analysed and the authenticity of the speech scrutinized.